1978
DOI: 10.1192/bjp.133.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Psychiatric Patients

Abstract: The study relates to suicides occurring in Shropshire during 1965 to 1973 inclusive. Psychiatric patients who had committed suicide were compared with others, matched by sex and age who had not done so. The suicide group included a higher proportion of members who had behaved violently, experienced a broken marriage (through death, separation or divorce) or earlier had deliberately harmed themselves, often by dangerous means. Of the psychiatric patients who committed suicide 63 per cent had seen a doctor withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In the series of Myers & Neal (22), only 14 % of 44 depressed psychiatric out-patient suicides were treated at the time of their suicidal action with a sufficient dose of antidepressants; 50 % of these patients were given no antidepressants, receiving in most cases barbiturates or benzcdiazepines. The corresponding figure given by Roy (24) is 36 % of depressed psychiatric in-and outpatients receiving antidepressive therapy at the time of their suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the series of Myers & Neal (22), only 14 % of 44 depressed psychiatric out-patient suicides were treated at the time of their suicidal action with a sufficient dose of antidepressants; 50 % of these patients were given no antidepressants, receiving in most cases barbiturates or benzcdiazepines. The corresponding figure given by Roy (24) is 36 % of depressed psychiatric in-and outpatients receiving antidepressive therapy at the time of their suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The question of adequate antidepressant therapy in depressed suicides (mainly out-patients) has been addressed by several authors. Their results point to the inadequacies of the drug treatment these patients receive (22)(23)(24).…”
mentioning
confidence: 94%
“…High suicide rates are particularly associated with acute episodes of illness,2 recent hospital discharge, 34 social factors such as living alone,5 and features of clinical history such as substance misuse6 and non-fatal self harm 7. However, comparatively little is known about the clinical care being provided to psychiatric patients before suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Myers and Neal [3] have also observed that about 30% of psychiatrically ill patients were also physically ill before committing suicide.…”
Section: Introductionmentioning
confidence: 99%